Hematopoietic Stem Cell Transplantation Restores Naïve T-Cell Populations in Atm-Deficient Mice and in Preemptively Treated Patients With Ataxia-Telangiectasia - Duecker, Ruth; Baer, Patrick C.; Buecker, Aileen; Huenecke, Sabine; Pfeffermann, Lisa-Marie; Modlich, Ute; Bakhtiar, Shahrzad; Bader, Peter; Zielen, Stefan; Schubert, Ralf (Frontiers in Immunology, 2019)
Background: Ataxia-telangiectasia (A-T) is a multisystem disorder with progressive cerebellar ataxia, immunodeficiency, chromosomal instability, and increased cancer susceptibility. Cellular immunodeficiency is based on naïve CD4+ and CD8+ T-cell lymphopenia. Hematopoietic stem cell transplantation (HSCT) offers a potential to cure immunodeficiency and cancer due to restoration of the lymphopoietic system. The aim of this investigation was to analyze the effect of HSCT on naïve CD4+ as well as CD8+ T-cell numbers in A-T. Methods: We analyzed total numbers of peripheral naïve (CD45RA+CD62L+) and memory (CD45RO+CD62L−) CD4+ and CD8+ T-cells of 32 A-T patients. Naïve (CD62LhighCD44low) and memory (CD62LlowCD44high) T-cells were also measured in Atm-deficient mice before and after HSCT with GFP-expressing bone marrow derived hematopoietic stem cells. In addition, we analyzed T-cells in the peripheral blood of two A-T patients after HLA-identic allogeneic HSCT. Results: Like in humans, naïve CD4+ as well as naïve CD8+ lymphocytes were decreased in Atm-deficient mice. HSCT significantly inhibited thymic lymphomas and increased survival time in these animals. Donor cell chimerism increased up to more than 50% 6 months after HSCT accompanied by a significant increase of naïve CD4 and CD8 T-cell subpopulations, but not of memory T-cells. This finding was also identified in the blood of the A-T patients after HSCT. Conclusion: HSCT seems to be a feasible strategy to overcome immunodeficiency and might be a conceivable strategy to avoid T-cell driven cancer in A-T at higher risk for malignancy. Naïve CD4 and CD8 T-cells counts are suitable markers for monitoring immune reconstitution post-HSCT. However, risks and benefits of HSCT in A-T have to be properly weighted.